A Study on Literature of Modern Indian English Novels: A Historical Analysis of Indian English Novels (Journal of Advances and Scholarly Researches in Allied Education, 2014)
This paper would present a brief overview of Indian English novels, focusing on the creation of the Indian English novel, which is really the tale of evolving India. The chapter shows how Mulk Raj Anand, Raja Rao and R.K. came with the great Indian trio. Narayan started his journey with the Indian English book. The early novels were imperialist descriptions of Indians but India rose up from its own stain of nationalism in an emergency with the rise of Indian independence and the Indian language started to shift. The whole situation of Indian English novels was turbulent. He opened the gate to a multitude of writers. This article would analyse and establish the big developments in Indian English novels that reflect on the recent patterns in Indian English novels.